Quadrivium in Varro’s Disciplines - Larionova, Sofia (Hyperboreus, 2021)
This article brings together the evidence concerning the subjects of the quadrivium in Varro’s Disciplines and provides a description of the book’s content, composition, and sources, while at the same time discussing the level of post-school mathematical education in Varro’s time. Polarizing views exist on the matter of post-school mathematical education, with some scholars placing it as early as the beginning of the Hellenistic period, and others linking its emergence to Neoplatonic circles in the fourth century CE. I argue that it is possible to attest to the existence of post-school mathematical education in the ﬁrst century BCE, even though it was pretty basic in nature and did not go beyond the fundamentals of the subjects of the quadrivium, as the contents of Varro’s book suggest. The ﬁrst section of the article covers Varro’s unconventional views on the origin of geometry: Varro rejects the Egyptian origin of geometry and traces its invention back to the dawn of human civilization. The second section deals with Varro’s geometrical deﬁnitions and their relation to the Euclidean tradition, showing that among his sources, there deﬁnitely were some Hellenistic introductions to μαθήματα. The ﬁnal section focuses on Varro’s conception of optics and canonics; here, his approach to canonics is identiﬁed as mostly mathematical with some empirical features.